P654 Clinical outcomes in familial versus sporadic inflammatory bowel disease diagnosed in the era of biological therapies. Prospective data from the ENEIDA registry. (21st January 2022) - González Muñoza, C; Calafat, M; Gisbert, J P; Iglesias, E; Minguez, M; Sicilia, B; Esteve, M; Gomollon, F; Calvet, X; Ricart, E; Carpio, D; Rivero, M; et al.
Abstract: Background: It has been reported that familial aggregation occurs in 10–20% of inflammatory bowel disease (IBD) patients1. Familial IBD has been associated with disease anticipation2 and with an increased need for immunosuppressants3 and surgery4. However, most studies were performed before the widespread use of biological agents and this may impact on the need for surgery. We aimed to compare the clinical outcomes of IBD (by means of the need for biological therapy and abdominal surgery) between familial and sporadic forms of IBD in the era of biological therapies. Methods: Data were extracted from the ENEIDA registry by GETECCU, a Spanish, prospectively-maintained, IBD database in which more than 80 centers are participating. Only adult patients diagnosed with IBD since 2005 and prospectively followed in the registry since diagnosis were included. Familial IBD was defined as those cases with at least one first-degree relative diagnosed with IBD. Sporadic IBD was defined as those cases with no familial relative (of any degree) with IBD. Kaplan-Meier survival curves were performed to evaluate the cumulative probabilities of remaining biologic-free and surgery-free. Log-rank test was performed to compare them between familial and sporadic IBD forms. Chi-square test was performed for the rest of variables. Results: A total of 5, 263 patients (2, 627 Crohn's disease [CD]; 2, 636 ulcerative colitis [UC]) were included. Of them, 507 (10%) were familial cases (274 CD, 233 UC; P=0.05). The median follow-up was 38, 4 and 35.5 months, respectively (P=0.086). Familial cases were younger (P=0.022) and had a higher proportion of females among UC cases (P=0.048). No differences were observed in the need for biological therapy in both CD and UC between familial and sporadic IBD. Regarding surgery, no differences were observed in the cumulative probabilities of a first intestinal resection for CD and colectomy for UC. Similar results were obtained when all the analyses were restricted to those subgroups at high-risk for surgery (i.e. CD with ileal involvement and extensive UC). Conclusion: In patients diagnosed with IBD in the era of biological therapies, familial forms have the same requirements for biological agents and resectional surgery as sporadic forms. Therefore, familial aggregation does not seem to be a factor for a more aggressive disease.